Ekstraksi dan karakterisasi minyak dari kulit ikan patin (Pangasius hypophthalmus) - Nurjanah .; Sugeng Heri Suseno; Titot Bagus Arifianto (Depik, 2014)
Catfish is playing an important role in aquaculture production; it is one of the primary commodities of inlandfisheries industry. Catfish meat has a yield of 49% and resulted in 51% of waste products. Thus catfish waste product has potency as source of fish oil which riches of omega-3. The Purpose of this study was to evaluate the suitable extaction method to obtain the high quality of fish oil from catfish skin. Based on the oxidative quality analysis data obtained extraction temperature of 60C gives the best quality of fish oil with parameters such as peroxide value, free fatty acid, p-anisidine value, acid value and total oxidation of 38 meq/kg, 0.45%, 107,5 meq/kg, 895 mg KOH/kg and 187.5, respectively. The best yield was 18.75% which was obtained at extraction temperature of 75 C. It was concluded that best extraction at 60C, for 30 minutes, with solvent and sample ratio 1:1.